A critical review on lead-free hybrid materials for next generation piezoelectric energy harvesting and conversion. Issue 12 (15th June 2021) - Banerjee, Swagata; Bairagi, Satyaranjan; Wazed Ali, S.
Abstract: This article aims to provide a comprehensive review of lead-free hybrid nano materials based piezoelectric fillers. It narrates the basic concept of piezoelectricity and discusses the salient properties of piezoelectric materials. Piezoelectric materials divided into classes of ceramics (lead based and lead free), polymers and composites, have been discussed in detail. The potential environmental threat posed by lead (Pb) in the lead based piezoelectric materials have gradually shifted the focus to lead free piezoelectric materials. Hence, lead free piezoelectric materials have been the main focus of this review. Lead free hybrid fillers, to enhance the piezoelectric properties of composites, have been covered as an integral part of this review. This topic has been covered principally under headings of KNN based fillers, Bi based fillers, Ba based fillers and MoS2 based fillers. The effect of doping into piezoelectric fillers have also been discussed in detail. With piezoelectricity being used in different fields of applications, a part of this review elucidates the use of piezoelectric materials to cater to the needs of technology. A brief overview has been provided regarding the use of piezoelectric materials in energy harvesting, as sensor, actuators, transducers, in structural health monitoring and repair, and in biomedical applications. The future scope of piezoelectricity and piezoelectric materials in fulfilling the demands of technology has been discussed in the concluding part of the review.